Exploring the Potential of Fulvalene Dimetals as Platforms for Molecular Solar Thermal Energy Storage: Computations, Syntheses, Structures, Kinetics, and Catalysis. Issue 47 (3rd October 2014) - Börjesson, Karl; Ćoso, Dušan; Gray, Victor; Grossman, Jeffrey C.; Guan, Jingqi; Harris, Charles B.; Hertkorn, Norbert; Hou, Zongrui; Kanai, Yosuke; Lee , Donghwa; Lomont, Justin P.; Majumdar, Arun; et al.
Abstract A study of the scope and limitations of varying the ligand framework around the dinuclear core of FvRu2 in its function as a molecular solar thermal energy storage framework is presented. It includes DFT calculations probing the effect of substituents, other metals, and CO exchange for other ligands on ΔHstorage. Experimentally, the system is shown to be robust in as much as it tolerates a number of variations, except for the identity of the metal and certain substitution patterns. Failures include 1, 1′, 3, 3′‐tetra‐tert‐butyl (4), 1, 2, 2′, 3′‐tetraphenyl (9), diiron (28), diosmium (24), mixed iron‐ruthenium (27), dimolybdenum (29), and ditungsten (30) derivatives. An extensive screen of potential catalysts for the thermal reversal identified AgNO3–SiO2 as a good candidate, although catalyst decomposition remains a challenge.